Optimalisasi Potensi Santri Putri Pondok Lirboyo melalui Life Skill Hampers sebagai Strategi Pemberdayaan Ekonomi Berbasis Pesantren - Firsta Bagus Sugiharto; Moh. Thoif; Abdul Hamid; Tomas Surandoko; Samuel Umbu Lado; Raveena Festy Mamilah; Kamaria (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
This study aims to optimize the potential of female santri at Pondok Lirboyo through the implementation of life skill hampers as an economic empowerment strategy based on Islamic boarding schools. The background of this research stems from the need to improve the economic skills of female santri in the pesantren, in order to create economic independence that can support their lives outside the pesantren. The method used in this study is a qualitative approach with a case study, involving interviews, observations, and documentation as data collection techniques. The participants in this study are the female santri involved in the life skill hampers program, the pesantren caretakers, and other related parties. The results of the study indicate that the implementation of life skill hampers successfully enhanced the skills of female santri in areas such as handicrafts, product packaging, and small business management. This program also had a positive impact on the economic improvement of the santri by creating marketable products. The implications of this research highlight the importance of developing life skill hampers programs as part of economic empowerment based on pesantren, which can provide business opportunities and enhance the economic independence of santri. In conclusion, the life skill hampers program can be an effective solution in optimizing the potential of female santri at Pondok Lirboyo, opening sustainable economic opportunities that strengthen their welfare.